2001
DOI: 10.1103/physrevlett.87.132501
|View full text |Cite
|
Sign up to set email alerts
|

Alignment Delays in theN=ZNucleiK72

Abstract: The ground state rotational bands of the N = Z nuclei (72)Kr, (76)Sr, and (80)Zr have been extended into the angular momentum region where rotation alignment of particles is normally expected. By measuring the moments of inertia of these bands we have observed a consistent increase in the rotational frequency required to start pair breaking, when compared to neighboring nuclei. (72)Kr shows the most marked effect. It has been widely suggested that these "delayed alignments" arise from np-pairing correlations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…We find that ε 2 = +0.475 for 80 Zr, ε 2 = −0.175 for 82 Zr, and ε 2 = −0.200 for 84 Zr. These values are consistent with the experimental data: a strongly prolate shape β 2 > +0.4 for 80 Zr [50], |β 2 | ≈ 0.3 for 82 Zr [18], and |β 2 | ≈ 0.2 for 84 Zr [19]. There is a link between the two quadrupole deformation parameters ε 2 and β 2 , β 2 ≈ 0.95ε 2 [49].…”
Section: A Single-particle Levels and Ground-state Potential Energy supporting
confidence: 89%
See 1 more Smart Citation
“…We find that ε 2 = +0.475 for 80 Zr, ε 2 = −0.175 for 82 Zr, and ε 2 = −0.200 for 84 Zr. These values are consistent with the experimental data: a strongly prolate shape β 2 > +0.4 for 80 Zr [50], |β 2 | ≈ 0.3 for 82 Zr [18], and |β 2 | ≈ 0.2 for 84 Zr [19]. There is a link between the two quadrupole deformation parameters ε 2 and β 2 , β 2 ≈ 0.95ε 2 [49].…”
Section: A Single-particle Levels and Ground-state Potential Energy supporting
confidence: 89%
“…3. Experimental data clearly show that the first rotational alignment begins at I = 12 for 82 Zr [18], I = 10 for 84 Zr [19], and a higher spin for 80 Zr [50]. Therefore, it is understood that the rotation alignments induce the shape transitions in 80,84 Zr nuclei.…”
Section: Amppess Shape Transitions and Decay Out Of The Sd Bandsmentioning
confidence: 95%
“…Based on their experiments, de Angelis et al [121], Fisher et al [127], and Mȃrginean et al [128] (and previous work cited therein) suggested a delay of the crossing between the g-band and s-band in the N = Z=36, 38,40,42, 44 nuclides as compared to the N = Z + 2 isotopes. These results initiated several theoretical studies.…”
Section: Pure Isovector Pairingmentioning
confidence: 94%
“…After the year 2000, the rotational response of N ≈ Z nuclei was investigated in a number of experimental papers [127][128][129][130][131][132][133][134][135][136][137][138]. Afanasjev , Frauendorf and Ragnarsson [139,140], interpreted the rotational bands of the nuclides with A = 58 − 80 in a systematic way, where E 0 (ω, C) was calculated by means of cranked relativistic Hartree+Boguljubov (CRHB) [141].…”
Section: Pure Isovector Pairingmentioning
confidence: 99%
“…This type of correlations may also be, in principle, visible through changes in structure of rotational nuclear bands. For example, the significance of the so-called delayed alignments in N =Z nuclei is at present intensely investigated, both experimentally [2,3] and theoretically, e.g., see recent Refs. [4][5][6][7][8] and references cited therein.…”
mentioning
confidence: 99%